Penguatan Kelembagaan Organisasi HKBP Berbasis Sentralisasi Keuangan - Jonson Rajagukguk (Jurnal Ilmu Sosial Dan Politik, 2022)
Institutional HKBP as one of the largest churches in Indonesia or Southeast Asia is still continuing to strengthen governance. As we all know, the internal problems of HKBP as a church organization are still far from what we expect from good and smart governance. So far, the financial decentralization that has occurred in the HKBP has caused various internal problems and ripples. The policy of financial decentralization by giving full authority to churches in the regions, for example, has created income inequality, for example. Many clergy stay in the church with substantial financial resources. With the financial centralization, it is hoped that income distribution, transfer of clergy or pastors can run well and this will strengthen church institutions. With the financial centralization, it is hoped that the church organization can become a good organization so that the mission and vision of the church can run well.